Morphological diversity and phylogeny of the diatom genus Entomoneis (Bacillariophyta) in marine plankton: six new species from the Adriatic Sea. Issue 2 (7th March 2018) - Mejdandžić, Maja; Bosak, Sunčica; Nakov, Teofil; Ruck, Elizabeth; Orlić, Sandi; Gligora Udovič, Marija; Peharec Štefanić, Petra; Špoljarić, Igor; Mršić, Gordan; Ljubešić, Zrinka
Abstract : The diatom genus Entomoneis is known from the benthos and plankton of marine, brackish, and freshwaters. Entomoneis includes diatoms with a bilobate keel elevated above the valve surface, a sigmoid canal raphe, and numerous girdle bands. Owing mostly to the scarcity of molecular data for a diverse set of species, the phylogeny of Entomoneis has not been investigated in depth. The few previous studies that included Entomoneis were focused on broader questions and the available data were from a small number of either unidentified Entomoneis or well‐known species (e.g., E. paludosa ). Since the first description of new species combining both molecular and morphological characters ( E. tenera ), we have continued to cultivate and investigate Entomoneis in the plankton of the Adriatic Sea. Combined multigene phylogeny (SSU rDNA sequences, rbc L, and psb C genes) and morphological observations (LM, SEM and TEM) revealed six new Entomoneis species supported by phylogenetic and morphological data: E. pusilla, E. gracilis, E. vilicicii, E. infula, E. adriatica, and E. umbratica . The most important morphological features for species delineation were cell shape, the degree and mode of torsion, valve apices, the appearance and structure of the transition between keel and valve body, the ultrastructure and the shape of the girdle bands, and the arrangement and density of perforations along the valve and valvocopulae. Our results highlight the underappreciated diversity of Entomoneis and call for a more in‐depth morphological and molecular investigation of this genus especially in planktonic habitats.